Observation of vertical variability of black carbon concentration in lower troposphere on campaigns in Poland. (July 2016) - Chilinski, M.T.; Markowicz, K.M.; Markowicz, J.
Abstract: This study presents two methods for observation of black carbon (BC) vertical profiles in lower troposphere based on the micro-aethalometer AE-51. In the first method micro-aethalometer was carried by observer along trail on slope of mountain valley. Second method uses unmanned aerial vehicle as a platform for collecting data up to 1500 m above ground. Our study presents vertical profiles collected in and above Subcarphatian Wislok valley. Profiles measured on trial on slopes of Wislok valley, were collected during strong smog conditions during autumn/winter season, when BC concentration reached values above 60 μg/m 3 . The smog intensive layer is usually close to the surface (up to 100 m) as a results of surface inversion and the mountain breeze circulation, which during the night transports air pollution emitted from houses toward the valley's bottom. Usually the vertical profiles of BC concentration show significant reduction with the altitude, however, some multilayered structures are also observed during night time inversion conditions. It has found that smog condition can develop in clean air mass, and in those cases local pollution has significant impact on the columnar aerosol properties. During such conditions the aerosol optical depth shows diurnal cycle which is rather not observed in the long-term data. UAV flights in the lower troposphere were conducted during two sessions, one with clean polar air masses (BC concentration < 1 μg/m 3 ) and second with moderate aerosol conditions (BC concentration 1–5 μg/m 3 ). Profile of BC concentration shows stratification of absorbing aerosols in a shape of multi-layer structures similarly to the lidar/ceilometer signals. Highlights: Two measurement schemes for obtaining black carbon vertical profiles are proposed. Vertical profiles of black carbon were measured from unmanned aerial vehicles. Smog conditions in mountain valley where measured during hiking experiment. Measurements were conducted with micro-aethalometer.